(untitled) (BIRDEM Medical Journal, 2024)
Background: Turner syndrome (TS) is a chromosomal disorder caused by complete or partial X chromosome monosomy that manifests various clinical features depending on the genetic background of affected girls. This study was designed to describe the presentation and clinical spectrum of patients with Turner Syndrome to create awareness for early referral. Methods: Our study included karyotype-proven TS patients aged 0-18 years who attended the Paediatric Endocrinology & metabolism outpatient department of BIERDEM Women and Children Hospital during the years 2018-2022. Retrospective data on the initial presentation, clinical spectrum and chromosomal abnormalities of patients diagnosed with Turner syndrome were extracted from the departmental database. Results: A total number of sixty patients were diagnosed as Turner Syndrome during the study period. The mean age was 10.6±4.0 year. The mejority (63.4%) were diagnosed between 11-18 years, between 5 to 10 years of age 21.7% and 15 % were diagnosed before the age of 5 years. The common presentation complaints were short stature (75%), delayed puberty (50%) and among patients diagnosed before age one year pedal edema (8%). Common dysmorphic features were wide spaced nipple (41.6%), webbing of neck (35%), low hair line (25%), short neck (21.7%), increased carrying angle (20%) & hyperconvex nail (20%). Most of the patients presented with the karyotyping 45,XO (61.7%) followed by 46,XX/45,XO (217%). Among the associated comorbidities cardiac defects was the most common, occuring in 23.4 % of the TS cases. This was followed by dyslipidemias (10%), autoimmune hypothyroidism (8.3%), obesity (6.6%) and Type 1 DM (1.6%). Behavioral problem was found in 8.3% of patients with TS. Other manifestations included speech delay (5%), hearing problem (3.3%) and repeated otitis media (1.6%).Hypoplastic uterus with streaky ovaries were found in 91.6% cases & renal anomalies were found in 8.3% patient (horse shoe kidney 5%, hydronephrosis 1.6% & ectopic kidney in 1.6% case).Luteinizing hormone and follicular stimulating hormone was raised in 90% case with TS. Conclusions: The majority were diagnosed and referred to Paediatric Endocrinologists after 5 years of age. A high degree of clinical suspicion can help us diagnose these children earlier. If TS is diagnosed earlier, growth can be achieved up to their maximum potential and also identification and address of comorbidities will provide better life. BIRDEM Med J 2024; 14(1): 31-37